Radiomic Analysis of Tumour Heterogeneity Using MRI in Head and Neck Cancer Following Chemoradiotherapy: A Feasibility Study - Guha, Amrita; Anjari, Mustafa; Cook, Gary; Goh, Vicky; Connor, Steve (Frontiers in Oncology, 2022)
Abstract: Objectives: To evaluate interval changes in heterogeneity on diffusion-weighted apparent diffusion coefficient (ADC) maps and T1-weighted post-gadolinium (T1w post gad) MRI in head and neck carcinoma (HNSCC), with and without chemo-radiotherapy (CRT) response. Methods: This prospective observational cohort study included 24 participants (20 male, age 62.9 ± 8.8 years) with stage III and IV HNSCC. The primary tumour (n=23) and largest lymph node (n=22) dimensions, histogram parameters and grey-level co-occurrence matrix (GLCM) parameters were measured on ADC maps and T1w post gad sequences, performed pre-treatment and 6- and 12-weeks post CRT. Two-year treatment response at primary and nodal sites was recorded. Wilcoxon signed rank test was used to compare interval changes in parameters after stratifying for treatment response and failure (p < 0.001 statistical significance). Results: 23/23 primary tumours and 18/22 nodes responded to CRT at 2 years. Responding HNSCC demonstrated a significant interval change in ADC histogram parameters (kurtosis, coefficient of variation, entropy, energy for primary tumour; kurtosis for nodes) and T1w post gad GLCM (entropy and contrast in the primary tumour and nodes) by 6 weeks post CRT (p < 0.001). Lymph nodes with treatment failure did not demonstrate interval alteration in heterogeneity parameters. Conclusions: ADC maps and T1w post gad MRI demonstrate evolution of heterogeneity parameters in successfully treated HNSCC by 6 weeks post CRT, however this is not observed in lymph nodes failing treatment. Advances in Knowledge: Early reduction in heterogeneity is demonstrated on MRI when HNSCC responds to CRT.